Present trophic level of Lake Alserio (Northern Italy) and prospect for its recovery - Rosario MOSELLO; Silvia ARISCI; Michela ROGORA; Giuseppe MORABITO; Letizia GARIBALDI (Journal of Limnology, 2002)
Lake Alserio is located in the subalpine area of Northern Italy, in the Brianza region near Lake Como. In November 1999 an EU funded project was started with the aim of devising and implementing interventions leading to the recovery of the lake and the surrounding area, which is characterised by a high degree of biodiversity as regards species and natural habitats. Since the seventies, Lake Alserio has been affected by eutrophication, which has resulted in high phosphorus (P) concentrations (annual average in 1999: 80-100 μg P l-1). The EU project envisaged liming the lake with Ca(OH)2 to reduce P concentrations in the water. This paper presents and discusses the results of chemical analyses performed on the lake and its tributaries in the first year of the study (November 1999-November 2000). The efficiency of liming with Ca(OH)2 to reduce P concentrations in laboratory and enclosure experiments is also discussed. The present condition of Lake Alserio is between eutrophic and hypereutrophic. Anoxic conditions characterise the hypolimnic waters for a prolonged period (May - October) during summer stratification, with a consequent high P release from the sediments (summer P concentrations in the deep water are close to 1 mg P l-1). Inflowing waters are characterised by high contents of ammonium and phosphorus, showing the importance of domestic sewage in the lake catchment; external load is still too high to permit the water to reach mesotrophic condition, the ultimate goal of recovery. Results of the liming experiments suggest that the treatment, if applied to Lake Alserio, could accelerate its recovery, although the specific procedures to be employed are still to be defined. However, before these or any other remedial operations can be undertaken, the external P load must be reduced by completing the diversion of sewage from the lake.